Pemberdayaan Masyarakat Desa Kaliyoso melalui Program Kerja KKN Mahasiswa UIN Walisongo Semarang - Ani Fitriati; Ayu Fathia Nurhaliza; Abel Qurrota A’yuna; Arisa Septiana Putri; Habiba Dewi Sima Dini; Zidan Yusva Alaydrus; Rif'an Chotibul Umam; Rizqi Putri Kinanti; Sulistio Sulistio (Jurnal Pengabdian KOLABORATIF, 2025)
The Community Service (KKN) activities by UIN Walisongo Semarang students in Kaliyoso Village, Kangkung District, Kendal Regency. This KKN program aims to empower the community through activities in the fields of education, religion, environment, and health. Some of the main activities carried out include teaching programs and additional tutoring for children, preaching and religious studies for the community, environmental cleanliness actions, and planting herbal plants. The results of these activities show an increase in children's academic achievement through teaching programs, a deeper understanding of religion through preaching and religious studies, and a cleaner and healthier environment thanks to the cleanliness program. Planting herbal plants also succeeded in providing new knowledge to the community about the benefits of herbal plants for health. Active community participation in each program shows the success of KKN in providing real positive impacts. The success of each program is measured by the success of the event and the impact felt by the community after each program is held. In conclusion, KKN in Kaliyoso Village succeeded in achieving its goals and made a significant contribution to improving the quality of life of the community according to the parameters of each KKN program. Suggestions for future KKN are to continue and expand successful programs and pay attention to feedback from the community to improve the effectiveness and impact of the program.